Check your sleep before you start: A secondary analysis of a stress management intervention for caregivers of stem cell transplant patients. Issue 6 (31st March 2021) - Ravyts, Scott G.; Sannes, Timothy S.; Dzierzewski, Joseph M.; Zhou, Eric S.; Brewer, Benjamin W.; Natvig, Crystal; Laudenslager, Mark L.
Abstract: Objective: Caregiving for hematopoietic stem cell transplant (HSCT) patients is associated with significant physical and psychological sequelae. While psychosocial interventions may reduce caregiver burden, knowledge regarding which caregivers may benefit the most from such interventions is limited. The purpose of this secondary analysis was to examine whether HSCT caregivers' peritransplant sleep moderated the effect of a psychosocial intervention on depression and anxiety posttransplant. Methods: Participants included 135 caregivers (mean age = 54.23) who participated in randomized controlled trial and were assigned to receive either 8 weeks of Psychoeducation, Paced Respiration, and Relaxation (PEPRR) or treatment as usual (TAU). Sleep, depression, and anxiety were assessed using the Pittsburg Sleep Quality Index, the Center for Epidemiologic Studies Depression Scale, and the State‐Trait Anxiety Inventory, respectively. Caregiver symptoms were assessed at baseline (e.g., peritransplant period) and 6‐month posttransplant. Results: Baseline sleep quality (∆ R 2  = 0.04, p  = 0.002), sleep efficiency (∆ R 2  = 0.03, p  = 0.02), and sleep onset latency (∆ R 2  = 0.07, p  < 0.001) independently moderated the effect of group assignment on depression outcomes at the 6‐month follow‐up. Specifically, caregivers with poor sleep at baseline who received PEPRR reported significantly lower depression scores at follow‐up compared to caregivers with poor sleep who received TAU. By contrast, only sleep quality (∆ R 2  = 0.02, p  = 0.01) and sleep onset latency (∆ R 2  = 0.02, p  = 0.005) moderated the effect of the group assignment on anxiety. Conclusions: Psychosocial interventions for HSCT caregivers may buffer against psychological morbidity, particularly among caregivers with poor sleep quality.